Proceedings of IEEE International Solid-State Circuits Conference - ISSCC '94
DOI: 10.1109/isscc.1994.344659
|View full text |Cite
|
Sign up to set email alerts
|

A CMOS area image sensor with pixel-level A/D conversion

Abstract: A CMOS 64 × 64 pixel area image sensor chip using Sigma-Delta modulation at each pixel for A/D conversion is described. The image data output is digital. The chip was fabricated using a 1.2µm two layer metal single layer poly n-well CMOS process. Each pixel block consists of a phototransistor and 22 MOS transistors. Test results demonstrate a dynamic range potentially greater than 93dB, a signal to noise ratio (SNR) of up to 61dB, and dissipation of less than 1mW with a 5V power supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 5 publications
0
50
0
Order By: Relevance
“…In previous works, decimation was performed at the chip level [7], [8]. But this entails a high bit rate at the pixel output, which limits the bit resolution, frame rate, and window size.…”
Section: Decimator Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous works, decimation was performed at the chip level [7], [8]. But this entails a high bit rate at the pixel output, which limits the bit resolution, frame rate, and window size.…”
Section: Decimator Designmentioning
confidence: 99%
“…The first implementation of a delta-sigma pixel was reported by Fowler et al [7]. The main issue with their work was a high output bit rate, since decimation was done outside the pixel.…”
mentioning
confidence: 99%
“…The maximum resolution of the ADC is determined by the gain of the comparator, and the speed of the ADC is determined by both the gain and the bandwidth of the comparator. Assuming subthreshold operation" and that the early voltage and gate efficiency of all the transistors are the same, it can be shown that the gain of the comparator is approximately AV=() (6) where Veariy 5 the early voltage of the transistors, i is the gate efficiency of the transistors, and is the thermal voltage. Again using the same assumptions, it can be shown that the gain bandwidth of the comparator is approximately GBW= 'bzas , (7) 8ir---output where 'bias 5 the tail current of the differential pair, and is the output capacitance of the comparator.…”
Section: Mcbs Adcmentioning
confidence: 99%
“…In the mid-1970's, infrared focal plane arrays (IRFPAs) began to be developed for infrared imaging in military and astronomical applications [37,38]. A typical IRFPA consists of a detector array fabricated with a narrow bandgap semiconductor (nominal bandgap values of 0.25 eV to 0.1 eV) connected to a so-called silicon multiplexer.…”
Section: Photon Counting Hybrid Pixel Detectorsmentioning
confidence: 99%
“…In an integrating imaging system there is a clear separation between the time used to collect the charge resulting from the photon interactions and the time when this accumulated charge is read from the pixels and processed. This feature is exploited in both column-level [35,36] and pixel-level [37,38,39,40,41,42,43] ADCs to operate, respectively, all columns or all pixels in parallel. As a result, slower ADCs than those in the chip-level approach can be used.…”
Section: Pixel-level Analog-to-digital Convertersmentioning
confidence: 99%